Contemporary and emerging strategies for eliminating human African trypanosomiasis due to Trypanosoma brucei gambiense: review1. Issue 6 (12th March 2015) - Steinmann, Peter; Stone, Christopher M.; Sutherland, C. Simone; Tanner, Marcel; Tediosi, Fabrizio
Abstract Objectives To review current and emerging tools for Gambiense HAT control and elimination, and propose strategies that integrate these tools with epidemiological evidence. Methods We reviewed the scientific literature to identify contemporary and emerging tools and strategies for controlling and eliminating Gambiense HAT. Through an iterative process involving key stakeholders, we then developed comprehensive scenarios leading to elimination, considering both established and new tools for diagnosis, case treatment and vector control. Results Core components of all scenarios include detecting and treating cases with established or emerging techniques. Relatively more intensive scenarios incorporate vector control. New tools considered include tiny targets for tsetse fly control, use of rapid diagnostic tests and oral treatment with fexinidazole or oxaboroles. Scenarios consider the time when critical new tools are expected to become ready for deployment by national control programmes. Based on a review of the latest epidemiological data, we estimate the various interventions to cover 1380 600 km2 and 56 986 000 people. Conclusions A number of new tools will fill critical gaps in the current armamentarium for diagnosing and treating Gambiense HAT. Deploying these tools in endemic areas will facilitate the comprehensive and sustainable control of the disease considerably and contribute to the ultimate goal of elimination.